Dampak Organisasi dan Strategi Integrasi Sistem Rme Berbasis Simpus: Perspektif Hot-Fit dari Puskesmas Pisangan - Miftah Parid Firmansyah; Haifa Khoirunisa (Jurnal Ilmiah Kedokteran dan Kesehatan, 2025)
Electronic Medical Records EMR refer to healthcare documents created via a digital platform designed for the administration of medical records. The Community Health Center Management Information System SIMPUS is a structured system designed to furnish data that aids in making informed decisions regarding the administration of community health centers with the objective of reaching established activity goals. All community health centers must establish a community health center information system, which may be conducted either in an electronic or non-electronic manner, and SIMPUS can act as an effective instrument for the execution of the Energy Management Plan RME within community health centers. This study aims to assess the effectiveness of SIMPUS in implementing an electronic medical record system through the application of the HOT-Fit approach at the Pisangan Community Health Center. The research is descriptive in nature and uses quantitative methodology, with data collected through questionnaires administered to 34 officers directly involved with the SIMPUS system using a nonprobability sampling technique and saturated sampling method. The results showed that the effectiveness of SIMPUS utilization in the implementation of electronic medical records was classified as effective across all dimensions, specifically 68.00 percent for human aspects, 64.42 percent for organizational aspects, 67.48 percent for technological aspects, and 72.36 percent for net benefit aspects. Based on the implementation of the electronic medical record system through SIMPUS using the HOT-Fit method at the Pisangan Community Health Center, adequate effectiveness scores were obtained in all aspects. As a suggestion, it is recommended that a SIMPUS authentication system be designed and implemented using a one-person-one-user policy to maintain the confidentiality of medical record data.